Masculinity in Selected L-Men Advertisements - Albertus Sebastian Adi Prasetyo (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study analyzes how L-Men persuades its target market to buy its products through the use of a masculinity image in its two advertisements. The two advertisements which the writer studied are entitled “L-Men 2018: 2Go & Gain Mass: Men’s Guide” and “Iklan L-Men Gain Mass Terbaru 2014 Versi Albert Sultan”. In order to find out how masculinity is portrayed in the two advertisements, the researcher sets his analysis on the advertisements’ verbal and non-verbal expressions. In so doing, the researcher conducts his analysis using the theory of Multimodal Discourse Analysis. Within the findings, it is revealed that despite both advertisements are indeed portraying masculinity, how each advertisement shows what is seen as masculine is different from one another. One advertisement shows that masculinity is based on a man’s aesthetical appearance and the other advertisement shows that masculinity is based on the physical strength of a man. Keywords: Multimodal Discourse Analysis, Masculinity, Advertisement, L-Men